First record of Camarochilus confusus (Heteroptera: Pachynomidae) from Argentina, the second pachynomid and first Pachynominae registered for the country - Melo, María Cecilia (2022)
Fieldwork in two protected areas from northeastern Argentina (P.N. El Impenetrable in Chaco Province, and the P.N. Rio Pilcomayo in Formosa Province) exploring the Heteroptea fauna, resulted In the discovery of a Camarochilus confusus Harris 1930 male that was collected by sweeping the vegetation. The species belongs to the subfamily Pachynominae, representing the first record of the group in the country. Aphelonotus simplus Uhler 1894 (Aphelonotinae), was also collected using light traps, confirming Its occurrence In the Chaco ecoreglons In Argentina.